2017
DOI: 10.1108/sbr-01-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on CSR: the case of Egypt

Abstract: Purpose The purpose of this paper is to review the corporate social responsibility (CSR) concept in Egypt via six sub-purposes which are the operational definition, activities, corporations’ strategic direction, budgeting and drivers for and obstacles against CSR alongside the implications of the January 25th 2011’s revolution on the concept. Design/methodology/approach This research is a perception study adopting a mixed methodology. A sample of 20 corporate managers undertaking CSR activities had been inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Thus, the findings suggest that the shift in ESG ratings after the revolution, in which they became based on political and ideological motives (see Darrag and Crowther, 2017), contributes to a higher financial performance. However, this is a modest evidence given that the political changes have little to do with the market consequences of ESG ratings.…”
Section: The Market and Financial Reactions To Esg Performance After mentioning
confidence: 85%
See 3 more Smart Citations
“…Thus, the findings suggest that the shift in ESG ratings after the revolution, in which they became based on political and ideological motives (see Darrag and Crowther, 2017), contributes to a higher financial performance. However, this is a modest evidence given that the political changes have little to do with the market consequences of ESG ratings.…”
Section: The Market and Financial Reactions To Esg Performance After mentioning
confidence: 85%
“…After the recent political changes, ESG practices were expected to shift more toward the social duty and religious responsibility of corporations toward their communities. In this respect, Darrag and Crowther (2017) showed that the socioeconomic and political changes that Egypt faced could have implications for CSR disclosures. They argued that before the last revolutions, CSR practices had been undertaken by corporations with a high philanthropic direction and low governmental intervention to manage corporate practices.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…In this light, seeking organisational legitimacy and legitimation not only implies adopting CSR reporting practices to meet transactional motives in response to the expectations of one's immediate audiences but also towards reflecting an appreciation of the broader responsibilities and purposes of the company in addressing deficits in the delivery of public services. However, in our view, there has been very little research on this aspect, both from the perspective of analysing CSR reports and exploring perceptions of organisational managers during, or close to, periods of significant socio-political changes (Darrag and Crowther, 2017).…”
Section: Csr Reporting In Developing Countriesmentioning
confidence: 99%